Biodiversity reporting in South Africa: corporate disclosures in the mining and food sectors - Mansoor, Hafsa (My University, 2016)
Biodiversity is facing mass extinction and this is recognised as an increasingly important issue worldwide. Factors such as industrial activities, overpopulation, urbanisation and global warming contribute significantly to the increasing dangers. Many companies operate in the world’s most biodiverse regions, yet a lack in regulatory frameworks and knowledge of biodiversity has introduced significantly high biodiversity-related risks for these companies. Despite the increasing importance of the issue, corporations are shying away from accountability for their impact on biodiversity. In this thesis, the integrated and sustainability reports of the top 10 companies listed on the Johannesburg Stock Exchange from the mining and food sectors are analysed. These reports are analysed in order to determine the location and extent of biodiversity disclosures, as well as to illustrate the nature of biodiversity disclosures presented. It was found that biodiversity-related disclosures are minimal and where such disclosures are available, they are vague and refrain from holding the corporations accountable. In addition, there is an increasing trend of biodiversity-related disclosures in the sustainability reports. The study also takes a closer look at the nature of biodiversity disclosure. This research contributes to a small body of existing research in the field and is the first study to examine biodiversity disclosures in South Africa.
A research report submitted In partial fulfilment of the requirements for the degree of A Master of Commerce (Accountancy) University of the Witwatersrand 2015